1998
DOI: 10.1159/000013981
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phototherapy on Renal Blood Flow Velocity in Preterm Infants

Abstract: Mean renal blood flow velocity (RBFV) was studied with two-dimensional/pulsed Doppler ultrasound and relative renal vascular resistance (RVR) was calculated before, during, and after phototherapy treatment in 30 preterm infants (gestational age ≤32 weeks) who were treated for a minimum of 12 h with phototherapy for nonhemolytic hyperbilirubinemia. RBFV decreased, whereas RVR increased significantly after the initiation of phototherapy. In ‘healthy’ (nonventilated) infants RBFV and RVR returned to baseline valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
3
8
0
1
Order By: Relevance
“…Therefore, it is possible that phototherapy induces a reduction of left ventricular output, and the increase of CBFV is caused by the redistribution of blood flow to the organs. This seems to be confirmed by the reported lack of postprandial response of the intestinal blood flow [18,25] and by the decrease of renal blood flow [4] during phototherapy. On the contrary, LPT, which, in our study, shows the same efficacy versus CPT in reducing bilirubin levels in preterm infants with jaundice, does not induce changes in TEWL and in cerebral hemodynamics as a consequence of the minimal dose of visible light >530 nm and infrared ray irradiance.…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, it is possible that phototherapy induces a reduction of left ventricular output, and the increase of CBFV is caused by the redistribution of blood flow to the organs. This seems to be confirmed by the reported lack of postprandial response of the intestinal blood flow [18,25] and by the decrease of renal blood flow [4] during phototherapy. On the contrary, LPT, which, in our study, shows the same efficacy versus CPT in reducing bilirubin levels in preterm infants with jaundice, does not induce changes in TEWL and in cerebral hemodynamics as a consequence of the minimal dose of visible light >530 nm and infrared ray irradiance.…”
Section: Discussionsupporting
confidence: 59%
“…However, haemodynamic side effects have been reported. An increase in peripheral blood flow (Oh et al 1973, Wu et al 1974) and a decrease in cardiac output (Walther et al 1985, Benders et al 1999a), postprandial intestinal blood flow response (Yao et al 1994, Pezzati et al 2000, and renal blood flow velocity (Benders et al 1998a) have been described in infants during phototherapy. Moreover, a higher incidence of patent ductus arteriosus (Rosenfield et al 1986, Barefield et al 1993) and a re-opening of the ductus arteriosus (Benders et al 1998a(Benders et al , b, 1999a have been reported in infants treated with phototherapy.…”
mentioning
confidence: 99%
“…Hypertensive disease during pregnancy,17 non-steroidal anti-inflammatory drugs,18 19 ACE inhibitors,20 magnesium sulphate21 or antibiotics18 administered to the mother, and intrapartum asphyxia22 are the most common antenatal risk factors described. The range of postnatal risk factors is as broad as low GA and very low birth weight,4 23 small-for GA (SGA),24 respiratory distress syndrome,18 low Apgar score,18 22 arterial hypotension and hypovolaemia,6 phototherapy in ventilated infants,25 early onset infection,17 septicaemia,6 congenital anomalies of the kidney and urinary tract,33 and drugs (Cox-inhibitors infused6 9 12 18 24 26 or oral)27 and antibiotics 7 8 18…”
Section: Discussionmentioning
confidence: 99%